Endoscopic endonasal surgery for benign fibro‐osseous lesions of the pediatric skull base. (24th June 2015) - Stapleton, Amanda L.; Tyler‐Kabara, Elizabeth C.; Gardner, Paul A.; Snyderman, Carl H.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To describe the presentation, treatment, and outcomes of benign fibro‐osseous tumors involving the skull base in a pediatric population. Methods Retrospective chart review from January 2002 to September 2013 of pediatric patients (ages 0–18 years) who underwent endoscopic endonasal surgery (EES) for benign fibro‐osseous tumors involving the skull base. Results Fourteen patients were identified with an age range of 2.7 to 17.9 years (mean, 12.5 years). Six juvenile ossifying fibromas, five benign fibro‐osseous lesions, two osteomas, and one fibrous dysplasia were treated. Ocular symptoms and nasal obstruction were the most common presenting symptoms in nine (64%) and six (43%) of patients, respectively; five (36%) presented with proptosis and four (29%) with diplopia. Two (14%) patients had cranial nerve VI palsy. Transsellar and transclival approaches were used in five (36%) of patients. Orbital and optic nerve decompressions were the most common components of the approaches performed in nine (64%) of the surgeries. Gross total resection (GTR) was achieved with single‐stage surgery in 10 (71%) patients; two additional patients underwent staged GTR. Two intraoperative cerebrospinal fluid (CSF) leaks occurred and were repaired endoscopically. There were no postoperative CSF leaks or infectious complications. Two patients had transient diplopia, and two had transient diabetes insipidus, all of which resolved. The mean follow‐up was 13.8 months. Two patients had a recurrence, and both required additional EES achieving GTR. Conclusions EES for benign fibro‐osseous tumors of the skull base is a safe and effective treatment for excision of these lesions in the pediatric population. Level of Evidence 4. Laryngoscope, 125:2199–2203, 2015